2016
DOI: 10.1021/acs.jctc.6b00416
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Transition-Metal Empirical Parameters for Molecular Mechanical Force Fields

Abstract: Force-field parameters of the first row transition metals together with a few additional common elements such as those from the second (Rh, Ru) and third (Hg, Pt) rows of elements in ligated forms were determined based on the density functional theory calculations. Bonding characteristics were determined by averaging metal-ligand force constants in optimal geometries from several chosen complexes of each metal in the most common oxidation numbers and structural arrangements. Parameters of Lennard-Jones potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 29 publications
(57 reference statements)
1
27
0
3
Order By: Relevance
“… 654 In another approach, the VDW parameters can be fit to QM-derived PES. For example, in the work of Šebesta et al, 775 they parametrized the LJ potentials of TMs based on QM calculated PESs between the TM complexes and small molecules. They found that there is a flat minimum on the surface of their “least-square” fits (see Figure 56 ).…”
Section: Classical Modeling Of Metal Ions: the Bonded Modelmentioning
confidence: 99%
See 1 more Smart Citation
“… 654 In another approach, the VDW parameters can be fit to QM-derived PES. For example, in the work of Šebesta et al, 775 they parametrized the LJ potentials of TMs based on QM calculated PESs between the TM complexes and small molecules. They found that there is a flat minimum on the surface of their “least-square” fits (see Figure 56 ).…”
Section: Classical Modeling Of Metal Ions: the Bonded Modelmentioning
confidence: 99%
“… Surface of the least-squares fits (∑Δ 2 ) of atomic LJ parameters ε and r 0 (which is σ in eq 33 ) for Pt(II) complexes interacting with the testing molecules. Reprinted with permission from ref ( 775 ). Copyright 2016 American Chemical Society.…”
Section: Classical Modeling Of Metal Ions: the Bonded Modelmentioning
confidence: 99%
“…Charges were obtained from RESP calculations following DFT/B3LYP optimization. Calculated charges are: Hg: +0.968, S: À0.798, all C(bonded to 2 hydrogens): 0.173, all C(bonded to 3 hydrogens): 0.069. van der Waals parameters were taken from the work of Šebesta et al65 for Hg: e = 1.955 kcal mol À1 ; R = 2.8 Å.…”
mentioning
confidence: 99%
“…Also, the enthalpy and entropy of the formation process were measured by the isothermal titration calorimetry . In our previous computational study, we explored the aforementioned process confirming the thermodynamic characteristics of the reaction suggesting the detailed mechanism . We recognized also the importance of proton transfer (PT) as a key step for both primary metal‐adduct formation as well as for the consequent completing of the cross‐link structure.…”
Section: Introductionmentioning
confidence: 82%
“…[12] In our previous computational study, we explored the aforementioned process confirming the thermodynamic characteristics of the reaction suggesting the detailed mechanism. [13,14] We recognized also the importance of proton transfer (PT) as a key step for both primary metal-adduct formation as well as for the consequent completing of the cross-link structure. Therefore, we decided to examine the PT process as a separate reaction under the influence of hydrated metal cations and compare the reaction characteristics.…”
Section: Introductionmentioning
confidence: 99%